2010
DOI: 10.5551/jat.4796
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Internal Carotid Artery Occlusion in Ischemic Stroke

Abstract: Aim: Homocysteine is associated with increased arterial resistance and eventually causes luminal reduction. The purpose of the present study was to evaluate an association between the plasma concentration of total homocysteine (tHcy) and stenosis or occlusion of the internal carotid artery (ICA) in patients with ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…Increased homocysteine levels correlate with stenosis and occlusion of intracranial vessels in patients with ischemic stroke, and it also increases stroke risk 26,27. In the current study, no differences in homocysteine concentrations were found between cancer and noncancer patients with ischemic stroke.…”
Section: Discussioncontrasting
confidence: 58%
“…Increased homocysteine levels correlate with stenosis and occlusion of intracranial vessels in patients with ischemic stroke, and it also increases stroke risk 26,27. In the current study, no differences in homocysteine concentrations were found between cancer and noncancer patients with ischemic stroke.…”
Section: Discussioncontrasting
confidence: 58%
“…Folate is used to reduce plasma tHcy 26) , which was independently associated with increased cerebral arterial resistance 27) and internal carotid arterial occlusion 28) , as the present authors reported previously. Folate also had modulating activity on LPL 29) , an important determinant of HDL-cholesterol 30) .…”
Section: Discussionmentioning
confidence: 51%
“…It causes focal lacunar infarction and more diffuse ischaemia, referred to as leukoaraiosis [20]. Jeong and colleagues evidenced a direct influence of elevated homocysteine even on the large arteries, such as internal carotid artery [21].…”
Section: Cardiovascular Disordersmentioning
confidence: 98%